Transformações eclesiais e engajamento social nas circulares de Madre Clara (década de 1960) - Garcia, Josane dos Santos (2024)
This work aims to analyze the social and ecclesiastical content of Circular Letters1 of Mother Clara (1891-1975) in the Congregation of the Franciscan Sisters of Our Lady Aparecida (CIFA), within the 1960s, in a context mainly of change and transformation in Religious Life, both ecclesiastical and social. The research will investigate specific social and religious issues addressed in the circulars: such as social discrimination, the changes in religious life2 and the danger of communism, examining how Mother Clara encouraged the sisters' active participation in social, political and religious issues of the time and exploring the impact of these congregational messages on social activities and their role in transformation of society during the period covered. Madre Clara is the religious name of Morena de Azevedo e Souza, born on the 27th of October 1891, in the city of Santa Cruz do Sul/RS. She is the daughter of Vasco de Azevedo and Souza (1854-1909) and Florinda de Azevedo e Souza (1858-1926), who had eighteen children. His father was a republican politician in Santa Cruz do Sul, one of the organizers of the local directory of the Riograndense Republican Party3 (PRR) and its leader for more than twenty years (History Team, 2000). With the death of Vasco de Azevedo e Souza in 1909, the family moved to Porto Happy. Morena graduated as a teacher and, according to Congregation records, wanted to be a religious of the Franciscan Sisters of Penance and Christian Charity4 (IPCC), the only religious entity in Franciscan spirituality in Rio Grande do Sul since 1872. Due to the need in helping the mother who was sick gave up on joining the institution (Madre Clara, 2000).